Dynamic regulation of the voltage-gated Kv2.1 potassium channel by multisite phosphorylation. (25th October 2007) - Mohapatra, D.P.; Park, K.-S.; Trimmer, J.S.
Abstract : Voltage-gated K + channels are key regulators of neuronal excitability. The Kv2.1 voltage-gated K + channel is the major delayed rectifier K + channel expressed in most central neurons, where it exists as a highly phosphorylated protein. Kv2.1 plays a critical role in homoeostatic regulation of intrinsic neuronal excitability through its activity- and calcineurin-dependent dephosphorylation. Here, we review studies leading to the identification and functional characterization of in vivo Kv2.1 phosphorylation sites, a subset of which contribute to graded modulation of voltage-dependent gating. These findings show that distinct developmental-, cell- and state-specific regulation of phosphorylation at specific sites confers a diversity of functions on Kv2.1 that is critical to its role as a regulator of intrinsic neuronal excitability.